A Drosophila melanogaster cell line (S2) facilitates post-genome functional analysis of receptors and ion channels. - Towers, P.R.; Sattelle, D.B. (BioEssays, 2002)
The complete sequencing of the genome of the fruit fly Drosophila melanogaster offers the prospect of detailed functional analysis of the extensive gene families in this genetic model organism. Comprehensive functional analysis of family members is facilitated by access to a robust, stable and inducible expression system in a fly cell line. Here we show how the Schneider S2 cell line, derived from the Drosophila embryo, provides such an expression system, with the bonus that radioligand binding studies, second messenger assays, ion imaging, patch-clamp electrophysiology and gene silencing can readily be applied. Drosophila is also ideal for the study of new control strategies for insect pests since the receptors and ion channels that many new animal health drugs and crop protection chemicals target can be expressed in this cell line. In addition, many useful orthologues of human disease genes are emerging from the Drosophila genome and the study of their functions and interactions is another area for postgenome applications of S2 cell lines.